Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1172/jci67655
|View full text |Cite
|
Sign up to set email alerts
|

MerTK inhibition in tumor leukocytes decreases tumor growth and metastasis

Abstract: MerTK, a receptor tyrosine kinase (RTK) of the TYRO3/AXL/MerTK family, is expressed in myeloid lineage cells in which it acts to suppress proinflammatory cytokines following ingestion of apoptotic material. Using syngeneic mouse models of breast cancer, melanoma, and colon cancer, we found that tumors grew slowly and were poorly metastatic in MerTK -/-mice. Transplantation of MerTK -/-bone marrow, but not wild-type bone marrow, into lethally irradiated MMTV-PyVmT mice (a model of metastatic breast cancer) decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
170
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(190 citation statements)
references
References 56 publications
13
170
1
Order By: Relevance
“…These findings are consistent with previous reports indicating that loss of MerTK or its ligand Gas6 decreases tumor malignancy in transplantable tumor models in virgin mice, without affecting macrophage recruitment to tumors (31,63). The previous studies reported that adoptive transfer of MerTK-deficient bone marrow reduced tumor growth over the course of 20 weeks and altered tumor cytokine levels, although lung metastasis and efferocytosis were not reported in this model (31). Together, the current and previous studies suggest that MerTK inhibition reduces tumor malignancy through impaired efferocytosisinduced cytokine modulation.…”
Section: Decreased Wound-healing Cytokines In Postpartum Mertksupporting
confidence: 93%
See 3 more Smart Citations
“…These findings are consistent with previous reports indicating that loss of MerTK or its ligand Gas6 decreases tumor malignancy in transplantable tumor models in virgin mice, without affecting macrophage recruitment to tumors (31,63). The previous studies reported that adoptive transfer of MerTK-deficient bone marrow reduced tumor growth over the course of 20 weeks and altered tumor cytokine levels, although lung metastasis and efferocytosis were not reported in this model (31). Together, the current and previous studies suggest that MerTK inhibition reduces tumor malignancy through impaired efferocytosisinduced cytokine modulation.…”
Section: Decreased Wound-healing Cytokines In Postpartum Mertksupporting
confidence: 93%
“…Thus, our studies provide the first illustration to our knowledge of how efferocytosis promotes malignant cancer progression in the endogenous TME. These findings are consistent with previous reports indicating that loss of MerTK or its ligand Gas6 decreases tumor malignancy in transplantable tumor models in virgin mice, without affecting macrophage recruitment to tumors (31,63). The previous studies reported that adoptive transfer of MerTK-deficient bone marrow reduced tumor growth over the course of 20 weeks and altered tumor cytokine levels, although lung metastasis and efferocytosis were not reported in this model (31).…”
Section: Decreased Wound-healing Cytokines In Postpartum Mertksupporting
confidence: 93%
See 2 more Smart Citations
“…However, non-cancer cell expression of Mertk can influence tumor growth. In Mertk −/− hosts, MMTV-PyMT orthotopic grafts show delayed tumor growth, decreased pulmonary metastases, increased expression of proinflammatory cytokines IL-6 and IL-12 and increased infiltration of CD8 + T cells, suggesting a role for Mertk in early tumor development [54]. This is not true in all models, as CT26 colorectal carcinoma and 4T1 mammary carcinoma in BALB/c mice, and Panc02 pancreatic adenocarcinoma, 3LL lung adenocarcinoma and B16 melanoma in C57BL/6 mice backgrounds were not different between wild-type and Mertk −/− hosts [42].…”
mentioning
confidence: 99%